Metagenomic insights and biosynthetic potential of Candidatus Entotheonella symbiont associated with Halichondria marine sponges - Hiyoung Kim; Jiyeong Ahn; Jaebum Kim; Hahk-Soo Kang (Microbiology Spectrum)
ABSTRACT Korea, being surrounded by the sea, provides a rich habitat for marine sponges, which have been a prolific source of bioactive natural products. Although a diverse array of structurally novel natural products has been isolated from Korean marine sponges, their biosynthetic origins remain largely unknown. To explore the biosynthetic potential of Korean marine sponges, we conducted metagenomic analyses of sponges inhabiting the East Sea of Korea. This analysis revealed a symbiotic association of Candidatus Entotheonella bacteria with Halichondria sponges. Here, we report a new chemically rich Entotheonella variant, which we named Ca. Entotheonella halido. Remarkably, this symbiont makes up 69% of the microbial community in the sponge Halichondira dokdoensis. Genome-resolved metagenomics enabled us to obtain a high-quality Ca. E. halido genome, which represents the largest (12 Mb) and highest quality among previously reported Entotheonella genomes. We also identified the biosynthetic gene cluster (BGC) of the known sponge-derived Halicylindramides from the Ca. E. halido genome, enabling us to determine their biosynthetic origin. This new symbiotic association expands the host diversity and biosynthetic potential of metabolically talented bacterial genus Ca. Entotheonella symbionts.IMPORTANCEOur study reports the discovery of a new bacterial symbiont Ca. Entotheonella halido associated with the Korean marine sponge Halichondria dokdoensis. Using genome-resolved metagenomics, we recovered a high-quality Ca. E. halido MAG (Metagenome-Assembled Genome), which represents the largest and most complete Ca. Entotheonella MAG reported to date. Pangenome and BGC network analyses revealed a remarkably high BGC diversity within the Ca. Entotheonella pangenome, with almost no overlapping BGCs between different MAGs. The cryptic and genetically unique BGCs present in the Ca. Entotheonella pangenome represents a promising source of new bioactive natural products.